Pendekatan Maqasid Syariah Dalam Kebijakan Fiskal Untuk Kesejahteraan Sosial Dan Pembangunan Ekonomi Hijau : (Studi Kasus : PT. Bank Syariah Indonesia Tbk Tahun 2021-2023) - Dwi Fadhilah Umami; Fauzatul Laily Nisa (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to analyze the implementation of the Maqasid Shariah approach in fiscal policies to achieve social welfare and green economic development, focusing on the case study of PT. Bank Syariah Indonesia Tbk for the period 2021-2023. The research method employed is descriptive analytics with a qualitative approach. Data were obtained through documentation/library studies. Data analysis was conducted using Content Analysis techniques. The results of the study indicate that PT. Bank Syariah Indonesia Tbk has implemented the Maqasid Shariah approach in designing fiscal policies by considering aspects of social welfare and green economic development. The fiscal policies implemented have had a positive impact on societal welfare and have contributed to sustainable and environmentally friendly economic development. This research is expected to contribute to the understanding of the implementation of Maqasid Shariah in the context of Islamic finance and economics and serve as a reference for Shariah financial institutions in formulating fiscal policies oriented towards social welfare and green economic development. .